Altered dynamic functional network connectivity in levodopa‐induced dyskinesia of Parkinson's disease. (13th October 2022) - Si, Qianqian; Gan, Caiting; Zhang, Heng; Cao, Xingyue; Sun, Huimin; Wang, Min; Wang, Lina; Yuan, Yongsheng; Zhang, Kezhong
Abstract: Aims: The aim of this study was to clarify the dynamic neural activity of levodopa‐induced dyskinesia (LID) in Parkinson's disease (PD). Methods: Using dynamic functional network connectivity (dFNC) analysis, we evaluated 41 PD patients with LID (LID group) and 34 PD patients without LID (No‐LID group). Group spatial independent component analysis and sliding‐window approach were employed. Moreover, we applied a k‐means clustering algorithm on windowed functional connectivity (FC) matrices to identify reoccurring FC patterns (i.e., states). Results: The optimal number of states was determined to be five, the so‐called State 1, 2, 3, 4, and 5. In ON phase, compared with No‐LID group, LID group occurred more frequently and dwelled longer in strongly connected State 1, characterized by strong positive connections between visual network (VIS) and sensorimotor network (SMN). When switching from OFF to ON phase, LID group occurred less frequently in State 3 and State 4. Meanwhile, LID group dwelled longer in State 2 and shorter in State 3. No‐LID group occurred more frequently in State 5 and less frequently in State 3. Additionally, correlation analysis demonstrated that dyskinesia's severity was associated with frequency of occurrence and dwell time in State 2, dominated by inferior frontal cortex in cognitive executive network (CEN). Conclusion: Using dFNC analysis, we found that dyskinesia may be related to the dysfunctional inhibition of CEN on motor loops and excessive excitation of VIS and SMN, which provided evidence of the changes in brain dynamics associated with the occurrence of dyskinesia. Abstract : Using dFNC analysis, we found that dyskinesia may be related to the dysfunctional inhibition of cognitive executive network on motor loops and excessive excitation of visual network and sensorimotor network, which provided evidence of the changes in brain dynamics associated with the occurrence of dyskinesia.